Superparamagnetic strong anion exchange magnetic bead for virus enrichment as well as preparation method and application of superparamagnetic strong anion exchange magnetic bead
By modifying the amino and quaternary ammonium salts on polymer magnetic microspheres with epoxy groups, superparamagnetic anion exchange magnetic beads were prepared, which solved the problems of cumbersome operation of existing virus enrichment methods and low adsorption and elution efficiency, and achieved efficient and automated virus enrichment and elution effects.
Patent Information
- Application Number
- CN202411751613.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
AI Technical Summary
The existing virus enrichment methods are cumbersome and difficult to automate. The existing anion exchange magnetic bead preparation process is complex, and hydrophobic irreversible bonds may occur between the magnetic beads and the virus, resulting in difficulty in elution, or low adsorption efficiency and elution efficiency.
Superparamagnetic anion exchange magnetic beads were prepared by using polymer magnetic microspheres with epoxy groups after amino modification and quaternary ammonium salt modification. The magnetic beads are modified by Fe3O4 magnetic core, SiO2 clad, and polyglycidyl methacrylate, combined with the modification of polyamino compounds and epoxy quaternary ammonium salts, thereby improving the hydrophilicity and adsorption capacity of the magnetic beads.
It achieves efficient virus enrichment and elution, which is significantly better than traditional magnetic beads, has excellent adsorption and elution capabilities, and can effectively adsorption and separation of multiple viruses.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bionanomaterials, and in particular to superparamagnetic strong anion exchange beads for virus enrichment, and a preparation method and application thereof. Background Art
[0002] Rapid, accurate, efficient, economical and simple virus enrichment and detection are prerequisites for early warning and prevention of viral disease outbreaks. Virus biological research usually requires the separation of intact virus particles from diluted samples. Currently, the most commonly used virus isolation methods are polyethylene glycol precipitation, membrane adsorption or ultrafiltration. Due to the limitations of the method principles, the above methods are cumbersome to operate, difficult to implement, and difficult to automate.
[0003] The magnetic bead method can be used to enrich the virus quickly and efficiently. This method achieves the enrichment and elution of the virus by controlling the binding and separation of magnetic beads and viruses under the action of a magnetic field. CN114200127A couples hepatitis B virus antibodies to carboxyl-modified superparamagnetic nanoparticle beads, which are used to bind to hepatitis B virus-positive serum or plasma, and then obtain enriched and concentrated hepatitis B virus. CN108486069A enriches porcine epidemic diarrhea virus (PEDV) by coupling PEDV membrane protein-specific single-domain antibodies to the surface of nanomagnetic beads; immunomagnetic beads can be used for rapid and effective separation. Then, immunomagnetic beads can only enrich and separate a single virus, and require the use of expensive antibodies, which is expensive and cannot meet the requirements for simultaneous enrichment and separation of multiple viruses.
[0004] Anion exchange magnetic beads reversibly bind to negatively charged virus particles, but the existing anion exchange magnetic bead preparation process is complicated, and hydrophobic irreversible binding may occur between the magnetic beads and the virus, making elution difficult; or there are problems such as low adsorption efficiency and elution efficiency. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide superparamagnetic strong anion exchange beads for virus enrichment, and a preparation method and application thereof.
[0006] The present invention provides superparamagnetic strong anion exchange magnetic beads, which are obtained by sequentially modifying polymer magnetic microspheres with epoxy with amino groups and quaternary ammonium salts;
[0007] The polymer magnetic microspheres having epoxy groups include:
[0008] Fe3O4 magnetic core; and
[0009] SiO2 wrapped around a Fe3O4 magnetic core; and
[0010] γ-methacryloxypropyltrimethoxysilane modified on SiO2; and
[0011] Poly(glycidyl methacrylate) formed by in situ polymerization of γ-methacryloxypropyltrimethoxysilane.
[0012] Specifically, the polymer magnetic microspheres having epoxy groups described in the present invention are prepared by the following steps:
[0013] Step 1, preparing Fe3O4 magnetic core by FeCl3·6H2O;
[0014] Step 2, using Fe3O4 as the magnetic core and tetraethyl orthosilicate (TEOS) as the silicon source to prepare core-shell structured Fe3O4@SiO2 magnetic microspheres;
[0015] Step 3, using γ-methacryloxypropyltrimethoxysilane (MPS) as a surface modification reagent to modify the surface of Fe3O4@SiO2 magnetic microspheres to prepare Fe3O4@SiO2-MPS magnetic microspheres with rich double bonds on the surface;
[0016] Step 4: In situ polymerization of glycidyl methacrylate (GMA) was carried out on the surface of Fe3O4@SiO2-MPS magnetic microspheres to prepare Fe3O4@SiO2@PGMA magnetic microspheres with (surface-rich) epoxy groups.
[0017] The mass ratio of the FeCl3.6H2O, TEOS, MPS and GMA is 1:0.35~0.65:0.40~0.60:0.60~1.20; specifically 1:0.40:0.50:0.80.
[0018] More specifically, the polymer magnetic microspheres with epoxy groups described in the present invention (also referred to as poly(glycidyl methacrylate) magnetic microspheres in the present invention) are synthesized using the method in patent CN112007620A, and the specific synthesis steps are as follows:
[0019] 1. Using FeCl3·6H2O as raw material, Fe3O4 magnetic core was prepared by solvothermal method;
[0020] 2. Fe3O4@SiO2 magnetic microspheres were prepared by Stöber method using Fe3O4 as magnetic core and tetraethyl orthosilicate (TEOS) as silicon source;
[0021] 3. Fe3O4@SiO2 magnetic microspheres were surface modified with γ-methacryloxypropyltrimethoxysilane (MPS) to prepare Fe3O4@SiO2-MPS magnetic microspheres;
[0022] 4. On the surface of Fe3O4@SiO2-MPS magnetic microspheres, azobisisobutyronitrile (AIBN) was used as an initiator, glycidyl methacrylate (GMA) was used as a polymerization monomer, and N,N-methylenebisacrylamide (MBA) was used as a crosslinker to perform in-situ polymerization of GMA on the surface of Fe3O4@SiO2 magnetic microspheres to prepare Fe3O4@SiO2@PGMA.
[0023] The mass ratio of the FeCl3.6H2O, TEOS, MPS, AIBN, GMA and MBA is 1:0.35~0.65:0.40~0.60:0.015~0.040:0.60~1.20:0.15~0.35; specifically 1:0.40:0.50:0.025:0.80:0.25.
[0024] After preparing poly(glycidyl methacrylate) magnetic microspheres, the carboxyl magnetic microspheres were separated by a magnetic separator and washed repeatedly with purified water for at least 5 times. The poly(glycidyl methacrylate) magnetic microspheres were stored in purified water. The microspheres passed the quality inspection and had a particle size of 400-800 nm.
[0025] Furthermore, the particle size of the superparamagnetic strong anion exchange magnetic beads is 400-800 nm;
[0026] In the present invention, the superparamagnetic strong anion exchange magnetic beads have the following structure:
[0027] X-R1-(CH2) n -R2-Y (Formula I); wherein
[0028] X is a polymer magnetic microsphere having a carboxyl group;
[0029] Y is a quaternary ammonium salt group;
[0030] R1-(CH2)n-R2 is a spacer arm;
[0031] R1 is selected from a primary amine group or a secondary amine group; specifically, R1 is a primary amine group;
[0032] R2 is selected from a primary amine group or a secondary amine group; specifically, R2 is a primary amine group;
[0033] Wherein n is an integer from 1 to 6; further, in a specific embodiment of the present invention, n is 3.
[0034] The present invention provides a method for preparing the superparamagnetic strong anion exchange magnetic beads, which comprises the following steps:
[0035] Step 1, the polymer magnetic microspheres having epoxy groups are modified by amino groups to obtain amino-modified polymer microspheres;
[0036] Step 2: The amino-modified polymer microspheres are modified with quaternary ammonium salts to obtain the superparamagnetic strong anion exchange magnetic beads.
[0037] Furthermore,
[0038] The amino modification can introduce different amounts of primary amine or secondary amine groups on the surface of the polymer magnetic microspheres as spacer arms of the structure shown in (Formula I). The amount of the primary amine or secondary amine groups can be controlled by adjusting the type, amount, reaction temperature or reaction time of the amination reagent.
[0039] The aminating agent is a polyamino compound;
[0040] In the present invention, the polymer magnetic microspheres modified with amino groups to have carboxyl groups react with polyamino compounds;
[0041] The polyamino compound is selected from one or more of ethylenediamine, 3,3-diaminodipropylamine, diethylenetriamine, triethylenetetramine and / or polyethyleneimine;
[0042] In a specific embodiment of the present invention, the polyamino compound is 3,3-diaminodipropylamine;
[0043] The mass ratio of the polymer magnetic microspheres with epoxy and 3,3-diaminodipropylamine is 1:1 to 1:2. Specifically, the mass ratio of the polymer magnetic microspheres with epoxy and 3,3-diaminodipropylamine is 1:1;
[0044] The reaction conditions are: using ethanol as the reaction solvent, nitrogen environment, 40-80° C. for 4-24 h.
[0045] In a specific embodiment of the present invention, the reaction conditions are: using ethanol as the reaction solvent, nitrogen environment, and reacting at 70° C. for 8 h.
[0046] The amino modification further includes the steps of magnetic separation and washing;
[0047] The washing reagents are ethanol and pure water;
[0048] The washing is performed by sequentially washing with ethanol and pure water; those skilled in the art may adjust the number of washing times according to actual conditions, and the present invention does not limit this.
[0049] The quaternary ammonium salt modification is that the amino-modified polymer microspheres react with epoxy quaternary ammonium salts;
[0050] The epoxy quaternary ammonium salt is selected from at least one of 2,3-epoxypropyltrimethylammonium chloride and / or 3,4-epoxybutyltrimethylammonium chloride;
[0051] In a specific embodiment of the present invention, the epoxy quaternary ammonium salt is 2,3-epoxypropyltrimethylammonium chloride;
[0052] The mass ratio of the amino-modified polymer microspheres to 2,3-epoxypropyltrimethylammonium chloride is 1:0.5 to 1:2.0. Specifically, the mass ratio of the amino-modified polymer microspheres to 2,3-epoxypropyltrimethylammonium chloride is 1:1;
[0053] The reaction conditions are: alkaline environment, 30-80° C., reaction time 4-24 h.
[0054] Specifically, sodium hydroxide with a final concentration of 0.1 M to 1.0 M is added to maintain an alkaline environment;
[0055] In a specific embodiment of the present invention, the reaction conditions are: using 0.5 M sodium hydroxide solution as the reaction solvent and reacting at 40° C. for 4 hours.
[0056] The quaternary ammonium salt modification further includes the steps of magnetic separation and washing;
[0057] The washing is performed by sequentially washing with ethanol and pure water until the washing liquid is neutral; those skilled in the art may adjust the number of washing times according to actual conditions, and the present invention does not limit this.
[0058] In the present invention, in each independent reaction, fully mixing the substances involved in the reaction is a conventional step adopted by those skilled in the art; the mixing method includes: ultrasound, vibration or stirring, etc.; those skilled in the art can appropriately adjust the mixing time according to actual conditions, and the present invention is not limited to this.
[0059] In a specific embodiment of the present invention, the method for preparing the superparamagnetic strong anion exchange magnetic beads comprises the following steps:
[0060] S1. The polymer magnetic microspheres with epoxy groups are dispersed in an organic solvent or pure water, ultrasonically dispersed for 5-10 minutes, a certain amount of polyamino compounds are added, and the mixture is transferred to a constant temperature water bath. The mixture is heated to 40-80°C under a nitrogen atmosphere and stirred for reaction for 4-24 hours. After the reaction, the mixture is magnetically separated, washed several times with ethanol and pure water, and stored in pure water to obtain a dispersion containing amino-modified polymer magnetic microspheres.
[0061] S2. Add a certain amount of sodium hydroxide to the dispersion containing amino-modified polymer magnetic microspheres, adjust the concentration of sodium hydroxide to 0.1~1.0 M, ultrasonically disperse for 5~10 minutes, add a certain amount of epoxy quaternary ammonium salt, transfer to a constant temperature water bath, heat to 30~80℃ under nitrogen atmosphere, stir and react for 4~24 hours. After the reaction is completed, magnetic separation, wash with ethanol and pure water in turn until neutral, and store in 10 mM sodium chloride solution to obtain superparamagnetic strong anion exchange magnetic beads.
[0062] The present invention prepares the superparamagnetic strong anion exchange magnetic beads of the present invention by using poly(styrene-glycidyl methacrylate) copolymer polymer magnetic microspheres, polyglycidyl methacrylate magnetic microspheres and silicon hydroxy magnetic microspheres and cores; the test results show that when the polyglycidyl methacrylate magnetic microspheres, that is, the polymer magnetic microspheres with epoxy groups of the present invention are polyglycidyl methacrylate magnetic microspheres, the prepared superparamagnetic strong anion exchange magnetic beads have the best adsorption capacity and elution capacity after adsorption, which are significantly better than the other two;
[0063] In addition, the present invention also adjusts the raw material ratio (such as the addition ratio of poly(glycidyl methacrylate) magnetic microspheres and 3,3-diaminodipropylamine and 2,3-epoxypropyltrimethylammonium chloride) and the parameters of the synthesis step (reaction time, etc.) in the preparation process of the superparamagnetic strong anion exchange magnetic beads; the test results show that the superparamagnetic strong anion exchange magnetic beads prepared by the steps and material ratios described in the present invention have the best performance and excellent virus adsorption and elution capabilities; at the same time, the superparamagnetic strong anion exchange magnetic beads described in the present invention can adsorb a variety of viruses, have a wide range of action, and have excellent adsorption and elution effects.
[0064] In the present invention, quaternary ammonium salt group can be introduced into silica magnetic bead or polymer magnetic bead surface by several methods. However, being limited by silica surface silanol quantity, directly modifying by the silane coupling agent containing quaternary ammonium salt, it is difficult to obtain higher quaternary ammonium salt density, therefore by screening, the superparamagnetic strong anion exchange magnetic beads that obtain poly(glycidyl methacrylate) magnetic microsphere vegetation can significantly reduce steric hindrance, improve and introduce quaternary ammonium salt group density, significantly improve the hydrophilicity of polymer magnetic microsphere matrix, and be easier to be dispersed in aqueous solution, meanwhile, the epoxy group on its surface is easy to modification, has reduced the difficulty of subsequent quaternary ammonium salt modification. By the modification of polyamino compounds, more reaction sites can be provided for the introduction of subsequent quaternary ammonium salt group. By the modification of epoxy quaternary ammonium salt, controllable introduction quaternary ammonium salt group under mild reaction condition can be achieved. During the amination and quaternary ammonium salt modification process, the hydrophilic hydroxyl groups formed by the ring opening of the epoxy groups will further enhance the hydrophilicity of the anion exchange magnetic beads. The introduced hydrophilic hydroxyl groups can further enhance the hydrophilicity of the anion cross-linked magnetic beads, making them more conducive to automated operation and enhancing their elution efficiency.
[0065] The invention provides a reagent containing magnetic beads, which comprises auxiliary materials and at least one of the superparamagnetic strong anion exchange magnetic beads of the invention or the superparamagnetic strong anion exchange magnetic beads prepared by the preparation method of the invention.
[0066] Furthermore, the auxiliary material includes at least one of a buffer, a stabilizer, an antioxidant, a preservative and / or an anticoagulant.
[0067] The present invention provides a kit, which comprises at least one of a binding solution, a cleaning solution and / or an elution solution and at least one of the following I) to III):
[0068] I), the superparamagnetic strong anion exchange magnetic beads of the present invention;
[0069] II), superparamagnetic strong anion exchange magnetic beads prepared by the preparation method of the present invention;
[0070] III), the reagent described in the present invention.
[0071] The present invention provides the use of at least one of the following i) to iv) in virus enrichment:
[0072] i) Superparamagnetic strong anion exchange magnetic beads of the present invention;
[0073] ii), superparamagnetic strong anion exchange beads prepared by the preparation method of the present invention;
[0074] iii), the reagent of the present invention;
[0075] iv), the kit of the present invention.
[0076] The viruses include lentivirus, adenovirus, novel coronavirus, African swine fever virus and viral vector, etc., which are not limited in the present invention.
[0077] The present invention provides a method for virus enrichment, which comprises enriching the virus using at least one of the following A) to D):
[0078] A), the superparamagnetic strong anion exchange magnetic beads of the present invention;
[0079] B), superparamagnetic strong anion exchange magnetic beads prepared by the preparation method of the present invention;
[0080] C), the reagent of the present invention;
[0081] D), the kit of the present invention.
[0082] The invention discloses a superparamagnetic strong anion exchange magnetic bead for virus enrichment and a preparation method thereof. The superparamagnetic strong anion exchange magnetic bead uses poly(glycidyl methacrylate) magnetic microspheres as raw materials, firstly introduces a large number of amino groups by reacting active epoxy groups with polyamino compounds, and then introduces abundant quaternary ammonium salt groups by reacting amino groups with epoxy quaternary ammonium salts under alkaline conditions. Through two epoxy ring-opening reactions, while introducing enough quaternary ammonium salt groups, a large number of hydrophilic hydroxyl groups are introduced on the surface of the magnetic microspheres, thereby improving the hydrophilicity of the anion exchange magnetic bead, and applying it to virus enrichment, the enrichment efficiency and elution efficiency are high, and the application prospect is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 The SEM image of the anion exchange magnetic beads obtained in Example 1 is shown;
[0084] Figure 2 The SEM image of the anion exchange magnetic beads obtained in Comparative Example 1 is shown;
[0085] Figure 3 The SEM image of the anion exchange magnetic beads obtained in Comparative Example 2 is shown;
[0086] Figure 4 Shown is the SEM image of Bioclone magnetic beads. DETAILED DESCRIPTION
[0087] The present invention provides superparamagnetic strong anion exchange beads for virus enrichment, preparation methods and applications thereof, and those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve. It should be particularly noted that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0088] In the present invention, the poly(glycidyl methacrylate) magnetic microspheres may also be polymer magnetic microspheres formed by copolymerization of glycidyl methacrylate and other monomers. The poly(glycidyl methacrylate) magnetic microspheres are produced by Suzhou Beaver Biomedical Engineering Co., Ltd. and have a multi-layer core-shell structure. The core is superparamagnetic ferroferric oxide with a diameter of about 200-400 nm, which is synthesized by a solvent thermal method; the middle layer is a silicon dioxide protective layer, which is synthesized by the Stöber method and is used to protect the magnetic substance; the outermost layer is a polymer layer, which is polymerized by glycidyl methacrylate or copolymerized by glycidyl methacrylate and other monomers, and the shell surface has abundant active epoxy groups. Preferably, the polymer magnetic microspheres have a three-layer core-shell structure and superparamagnetism, and have a large number of active epoxy groups on the surface and are not modified by other functional groups. The particle size of the poly(glycidyl methacrylate) magnetic microspheres used in the present invention is preferably 400-800 nm.
[0089] The test materials used in the present invention are all common commercial products and can be purchased on the market. The present invention is further described below in conjunction with the embodiments:
[0090] Example 1 Preparation of superparamagnetic strong anion exchange beads
[0091] The polymer magnetic microspheres used in this embodiment are poly(glycidyl methacrylate) magnetic microspheres, which are produced by Suzhou Beaver Biomedical Engineering Co., Ltd. The polymer magnetic microspheres are composed of a three-layer core-shell structure, wherein the core is a superparamagnetic ferroferric oxide microsphere with a diameter of 200-400 nm, which is synthesized by a solvent thermal method; the middle shell is a silicon dioxide protective layer with a shell thickness of about 50 nm, which is synthesized by the Stöber method and is used to protect the magnetic substance; the outermost layer is a polymer shell layer with a thickness of about 30 nm, which is prepared by a free radical polymerization method.
[0092] Prepare superparamagnetic strong anion exchange beads as follows:
[0093] S1. Aminated polymer magnetic microspheres: 20 g of polymer magnetic microspheres and 3200 mL of anhydrous ethanol were added to a 5000 mL three-necked flask. After being dispersed evenly by ultrasonic stirring, the microspheres were placed in a constant temperature water bath. 35 mL of 3,3-diaminodipropylamine was added. Nitrogen was passed through to deoxygenate for 10 minutes. The temperature was then raised to 70°C and the reaction was carried out at this temperature for 8 hours. The obtained amino-modified polymer magnetic microspheres were washed once with anhydrous ethanol and three times with distilled water and stored in distilled water for later use.
[0094] S2, quaternary ammonium salt modified polymer magnetic microspheres: The aminated polymer magnetic microspheres obtained in step S1 and 1600 mL of 0.5 M sodium hydroxide solution were added to a 3000 mL three-necked flask, and after being dispersed uniformly by ultrasonic stirring, they were placed in a constant temperature water bath, 20 g of 2,3-epoxypropyltrimethylammonium chloride was added, the temperature was raised to 40°C, and the reaction was carried out at this temperature for 4 hours. The obtained quaternary ammonium salt modified polymer magnetic microspheres, named mPGMA-Q, were washed with pure water until neutral, and stored in a 10 mM NaCl solution for later use.
[0095] The mPGMA-Q obtained in step S2 was subjected to SEM detection, and the detection results are shown in Figure 1 The obtained anion exchange magnetic beads were spherical nanoparticles with a smooth surface, no obvious agglomeration, uniform particle size distribution, and an average particle size of 484 nm. The quaternary ammonium salt group content was determined to be 250 μmol / g by titration.
[0096] Comparative Example 1 Comparative Preparation of Anion Exchange Magnetic Beads 1
[0097] The magnetic beads used are poly(styrene-glycidyl methacrylate) copolymer magnetic microspheres (the synthesis process of the magnetic beads is basically the same as the PGMA microspheres in the embodiment, the only difference is that the monomer GMA is replaced by St (styrene) and GMA (GMA is added one hour after St is added to the reaction), and the remaining steps and reagents used are the same; wherein the mass ratio of the FeCl3, TEOS, γ-methacryloxypropyltrimethoxysilane (MPS), St (styrene) and glycidyl methacrylate (GMA) is 1:0.40:0.50:0.60:0.205), produced by Suzhou Beaver Biomedical Engineering Co., Ltd., and are copolymer magnetic microspheres, which consist of a three-layer core-shell structure, the core of which is a superparamagnetic ferroferric oxide microsphere with a diameter of 200~400 nm, synthesized by a solvothermal method; the middle shell is a silica protective layer with a shell thickness of about 50 nm, synthesized by the Stöber method, and used to protect the magnetic material; the outermost layer is formed by copolymerization of styrene and glycidyl methacrylate, with a thickness of about 30 nm, prepared by free radical polymerization.
[0098] Prepare comparative anion exchange magnetic beads 1 as follows:
[0099] S1. Aminated copolymer magnetic microspheres: 20 g of copolymer magnetic microspheres and 3200 mL of anhydrous ethanol were added into a 5000 mL three-necked flask. After being dispersed evenly by ultrasonic stirring, the microspheres were placed in a constant temperature water bath. 30 mL of ethylenediamine was added and nitrogen was passed through to deoxygenate for 10 minutes. The temperature was then raised to 70°C and reacted at this temperature for 8 hours. The obtained amino-modified copolymer magnetic microspheres were washed once with anhydrous ethanol and three times with distilled water and stored in distilled water for later use.
[0100] S2, quaternary ammonium salt modified copolymer magnetic microspheres: The amino modified polymer magnetic microspheres obtained in step S1 and 1600 mL of 0.5 M sodium hydroxide solution were added to a 3000 mL three-necked flask, and after being dispersed uniformly by ultrasonic stirring, they were placed in a constant temperature water bath, 20 g of 2,3-epoxypropyltrimethylammonium chloride was added, the temperature was raised to 40°C, and the reaction was carried out at this temperature for 4 hours. The obtained quaternary ammonium salt modified copolymer magnetic microspheres were named mP(St-GMA)-Q, washed with a large amount of pure water until neutral, and stored in a 10 mM NaCl solution for later use.
[0101] The magnetic microspheres obtained in step S2 were subjected to SEM detection, and the detection results are shown in Figure 2 The obtained anion exchange magnetic beads were spherical nanoparticles with a rough surface, no obvious agglomeration, uniform particle size distribution, and an average particle size of 546 nm. The quaternary ammonium group content was determined to be 130 μmol / g by titration.
[0102] Comparative Example 2 Comparative Preparation of Anion Exchange Magnetic Beads 2
[0103] The magnetic beads used are silicon hydroxy magnetic microspheres, produced by Suzhou Beaver Biomedical Engineering Co., Ltd. (silicon dioxide hydroxy magnetic beads (Super 500 nm), item number: 70304). Silicon hydroxy magnetic microspheres are composed of a core-shell structure, the core of which is superparamagnetic ferroferric oxide with a diameter of 300-400 nm, synthesized by solvothermal method; the middle shell is a silicon dioxide protective layer with a shell thickness of about 50 nm, synthesized by Stöber method, and used to protect magnetic substances.
[0104] Prepare comparative anion exchange magnetic beads 2 as follows:
[0105] S1. Double-bond modified silanol magnetic microspheres: 4.0 g of silanol magnetic microspheres, 560 mL of ethanol and 48 mL of distilled water were added to a 1000 mL three-necked flask. After being dispersed evenly by ultrasonic stirring, the flask was placed in a constant temperature water bath. 2.4 mL of ammonia water and 6.0 mL of γ-methacryloxypropyltrimethoxysilane were added. Nitrogen was passed through to deoxygenate for 10 minutes. The temperature was then raised to 70°C and reacted at this temperature for 6 hours. The obtained double-bond modified silanol magnetic beads were washed three times with anhydrous ethanol and stored in anhydrous ethanol for later use.
[0106] S2. Preparation of polymethacryloxypropyltrimethoxysilane magnetic microspheres: 4.0 g of the double-bond modified silanol magnetic beads obtained in step S1, 560 mL of distilled water, 24 mL of ethanol, 0.168 g of sodium dodecylbenzenesulfonate, 10.2 mL of methacryloyloxyethyltrimethylammonium chloride, 2.4 g of methylenebisacrylamide, and 0.24 g of AIBN were added into a 1000 mL three-necked flask, and deoxygenated with nitrogen for 10 minutes. The temperature was then raised to 70°C and reacted at this temperature for 6 hours. The obtained polymethacryloxypropyltrimethoxysilane magnetic microspheres were named mPMAC, washed 3 times with anhydrous ethanol and 3 times with distilled water, and stored in 10 mM NaCl solution for later use.
[0107] The magnetic microspheres obtained in step S2 were subjected to SEM detection, and the detection results are shown in Figure 3 The obtained anion exchange magnetic beads were spherical nanoparticles with a smooth surface, uneven particle size distribution, obvious agglomeration between particles, and an average particle size of 468 nm. The quaternary ammonium group content was determined by titration to be 480 μmol / g.
[0108] Example 3 Enrichment effect of magnetic beads on new coronavirus
[0109] The virus used in this test example is a new coronavirus pseudovirus purchased from Xiamen Zhishan Biotechnology Co., Ltd., and magnetic beads are used to refer to mPGMA-Q, mP(St-GMA)-Q and mPMAC prepared in Example 1 and the comparative example.
[0110] Test method: Add a certain volume of magnetic bead suspension to the centrifuge tube, the concentration of magnetic beads is 10 mg / mL, magnetically absorb the liquid, add a certain volume of virus suspension, vortex to disperse evenly, and place it on a vertical mixer to mix for a certain time. After magnetic absorption, take 300 μL of supernatant for analysis and discard the rest of the supernatant. Add 300 μL of eluent (1×PBS solution containing 0.75 MKCl) to the above centrifuge tube, vortex to disperse evenly, place it on a vertical mixer to mix for 15 min, and take all the supernatant for analysis after magnetic absorption. The animal virus DNA / RNA extraction kit (Cat. No.: 70416II) produced by Suzhou Beaver Biomedical Engineering Co., Ltd. was used to extract viral DNA, and the virus concentration before and after adsorption was determined by the established quantitative PCR reaction system.
[0111] The calculation formulas for enrichment efficiency and elution efficiency are as follows:
[0112]
[0113]
[0114] (1) When the magnetic beads dosage is 10 mg and the virus concentration is 1×10 5 copy / mL, and the volume of the virus suspension was 10 mL, the effects of different magnetic beads on the virus enrichment efficiency were determined according to the above test method. The results are shown in Table 1: The enrichment efficiency of mPGMA-Q and mPMAC magnetic beads for the new coronavirus pseudovirus was relatively close, 99.95% and 99.50%, respectively, which were significantly higher than mP(St-GMA)-Q (79.46%). This may be due to the low content of quaternary ammonium groups in mP(St-GMA)-Q, resulting in its lower affinity for the virus. The elution data showed that when PBS solution containing 0.75 M KCl was used as the eluent, the elution efficiency of mPGMA-Q was 49.16%, which was significantly higher than that of mPMAC (32.26%) and mP(St-GMA)-Q (6.63%). This may be because: 1) mPGMA-Q has a uniform particle size, smoother morphology and a more moderate content of quaternary ammonium groups, which makes its binding force with the virus more moderate and is conducive to elution; 2) mPGMA-Q is more hydrophilic than mPMAC and mP(St-GMA)-Q, which reduces the hydrophobic interaction between the magnetic beads and the virus and is conducive to elution.
[0115] Table 1. Virus enrichment efficiency of different magnetic beads
[0116]
[0117] (2) When the virus concentration is 1×10 8When the volume of the virus suspension was 300 μL and the virus enrichment efficiency of mPGMA-Q magnetic beads of different masses was measured according to the above test method, the results are shown in Table 2. As the amount of magnetic beads increased, the adsorption efficiency gradually increased. When the amount of magnetic beads reached 0.1 mg (the concentration of magnetic beads was 0.33 mg / mL at this time), the adsorption efficiency reached 99.65%. If the amount of magnetic beads continued to increase, the enrichment efficiency remained basically unchanged.
[0118] Table 2. Virus enrichment efficiency of mPGMA-Q magnetic beads of different masses
[0119]
[0120] (3) When the virus concentration is 1×10 8 copy / mL, when the virus suspension volume was 300 μL, the enrichment efficiency of mPGMA-Q magnetic beads (0.1 mg) at different enrichment times was determined according to the above test method, and the results are shown in Table 3. It can be seen that at 5 min, the enrichment efficiency of mPGMA-Q magnetic beads for viruses can reach a maximum value of 99.9%, and as time increases, the enrichment efficiency remains unchanged.
[0121] The above data show that mPGMA-Q magnetic beads can efficiently enrich viruses in a short time.
[0122] Table 3. Enrichment efficiency of novel coronavirus at different enrichment times
[0123]
[0124] Comparative Example 3 Comparison with existing magnetic beads
[0125] Competitor magnetic beads: Bioclone magnetic beads (Cat. No.: FU-101)
[0126] A comparison of the enrichment and elution effects of the superparamagnetic strong anion exchange magnetic beads of the present invention and the magnetic beads of competing products on real African swine fever virus in different buffer solutions is shown in Table 3; a comparison of the enrichment and elution effects of the magnetic beads of the embodiment of the present invention and the magnetic beads of competing products on the new coronavirus in urban sewage is shown in Table 4.
[0127] Table 3. Enrichment and elution effects of BioBioclone magnetic beads and the superparamagnetic strong anion exchange magnetic beads of the present invention on real African swine fever virus in different buffer solutions
[0128]
[0129] Table 4. Comparison of the enrichment and elution effects of Bioclone magnetic beads and the superparamagnetic strong anion exchange magnetic beads of the present invention on the novel coronavirus in urban sewage
[0130]
[0131] The results show that under different conditions, the superparamagnetic strong anion exchange magnetic beads obtained by the present invention have a better enrichment effect on African swine fever virus than the competitive magnetic beads (Ct difference 1, the larger the difference, the stronger the enrichment ability), especially in sewage samples, the superparamagnetic strong anion exchange magnetic beads of the present invention still have a certain enrichment ability, while the competitive magnetic beads can hardly enrich. At the same time, even under almost the same enrichment conditions, the superparamagnetic strong anion exchange magnetic beads of the present invention are easier to elute (Ct difference 2, the smaller the difference, the better the elution ability).
[0132] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Superparamagnetic strong anion exchange magnetic beads, characterized in that, The polymer magnetic microspheres with epoxy groups are successively modified with amino groups and then with quaternary ammonium salts to obtain the nanostructured nanostructured nanostructured nanostructured nanospheres.
2. The superparamagnetic strong anion exchange magnetic beads according to claim 1, characterized in that: The polymer magnetic microspheres having epoxy groups include: Fe3O4 magnetic core; and SiO2 wrapped around a Fe3O4 magnetic core; and γ-methacryloxypropyltrimethoxysilane modified on SiO2; and Poly(glycidyl methacrylate) formed by in situ polymerization of γ-methacryloxypropyltrimethoxysilane.
3. The superparamagnetic strong anion exchange magnetic beads according to claim 1, characterized in that: The particle size is 400~800 nm.
4. The method for preparing superparamagnetic strong anion exchange magnetic beads according to any one of claims 1 to 3, characterized in that: The steps include: Step 1, modifying polymer magnetic microspheres having epoxy groups by amino groups to obtain amino-modified polymer magnetic microspheres; Step 2: The amino-modified polymer magnetic microspheres are modified with quaternary ammonium salts to obtain the superparamagnetic strong anion exchange magnetic beads.
5. The preparation method according to claim 4, characterized in that: The amino group is modified to react with polymer magnetic microspheres having epoxy groups and polyamino compounds; The reaction conditions are: using ethanol as the reaction solvent, nitrogen environment, 40-80° C. for 4-24 h; The quaternary ammonium salt is modified by reacting the amino-modified polymer magnetic microspheres with epoxy quaternary ammonium salts; The reaction conditions are: alkaline conditions, 30-80° C., reaction time 4-24 h.
6. The preparation method according to claim 5, characterized in that: The polyamino compound is 3,3-diaminodipropylamine; The mass ratio of the polymer magnetic microspheres having epoxy to 3,3-diaminodipropylamine is 1:1-1:
2. The epoxy quaternary ammonium salt is 2,3-epoxypropyltrimethylammonium chloride; The mass ratio of the amino-modified polymer magnetic microspheres to 2,3-epoxypropyltrimethylammonium chloride is 1:0.5-1:2.
0.
7. A reagent containing magnetic beads, characterized in that: The invention comprises at least one of the superparamagnetic strong anion exchange magnetic beads described in any one of claims 1 to 3 or the superparamagnetic strong anion exchange magnetic beads prepared by the preparation method described in any one of claims 4 to 6 and auxiliary materials.
8. A kit, characterized in that It includes at least one of a binding solution, a cleaning solution and / or an elution solution and at least one of the following I) to III): I), the superparamagnetic strong anion exchange magnetic beads according to any one of claims 1 to 3; II), superparamagnetic strong anion exchange magnetic beads prepared by the preparation method according to any one of claims 4 to 6; III), the reagent according to claim 7.
9. Application of at least one of the following i) to iv) in virus enrichment: i), the superparamagnetic strong anion exchange magnetic beads according to any one of claims 1 to 3; ii), superparamagnetic strong anion exchange beads prepared by the preparation method according to any one of claims 4 to 6; iii) the reagent according to claim 7; iv) The kit according to claim 8.
10. A method for virus enrichment, characterized in that: The method comprises enriching the virus using at least one of the following A) to D): A), the superparamagnetic strong anion exchange magnetic beads according to any one of claims 1 to 3; B), superparamagnetic strong anion exchange beads prepared by the preparation method according to any one of claims 4 to 6; C) the reagent according to claim 7; D) The kit according to claim 8.
Citation Information
Patent Citations
Virus isolation method for low-content sample of porcine epidemic diarrhea virus (PEDV)
CN108486069A
Preparation method of streptavidin magnetic microspheres
CN112007620A
Hepatitis B virus enrichment fluorescent PCR (polymerase chain reaction) detection method
CN114200127A
Cited By
Preparation method and application of multi-layer sandwich type carboxyl magnetic microspheres
CN120714598A
Nanometer magnetic bead based on polyamino acid material, preparation method of nanometer magnetic bead and application of nanometer magnetic bead in early cancer screening
CN122006677A